Marketing Politik dalam Pemilukada Kabupaten Karo Tahun 2010 - Nehemia Syaloom Ginting (Dinamika Politik, 2013)
This study is a study of the application of political marketing in the elections at Karo Regency in 2010. The focus is to discuss what is the basic of the success of political marketing strategy that undertaken by the campaign team of Kena Ukur Surbakti - Terkelin Brahmana in the elections at Karo Regency in 2010. The findings of this study, among others, there are two things on which the success of the political strategy adopted by the campaign team of Kena Ukur Surbakti - Terkelin Brahmana. Among other things: first, the campaign team of Kena Ukur Surbakti - Terkelin Brahmana strengthening the base of political marketing to areas where the majority of voters are traditionally the rural areas, and second, campaign team Kena Ukur Surbakti - Terkelin Brahmana highlight ethnicity as a key issue to attract support from the community. The method used is descriptive-qualitative method that is intended to describe an event in more detail. Key Words: marketing politics, voting behavior, the issue of ethnicity.